(untitled) (Bangladesh Journal of Neuroscience, 2018)
Background: Stroke is responsible for the highest mortality and disability among adult population in Bangladesh. With a death rate of 125.6 per 100,000 populations, Bangladesh ranks 34th globally for stroke related death. This study was aimed to find out association of plasma BNP with acute ischemic stroke severity which may help in management of these patients. Methods: This cross-sectional study was conducted in the Department of Neurology, BSMMU, Dhaka from June 2018 to October 2019. Total 45 subjects with history within 7 days and confirmed by CT scan of head or MRI of brain were selected purposively from the Neurology departments of BSMMU, NINS&H and Internal Medicine department of DMCH, Dhaka, Bangladesh. Venous blood samples were collected from these patients and analyzed at the Department of Biochemistry and Molecular Biology, BSMMU, Dhaka for estimation of plasma BNP. Results: This study found increased plasma BNP of >100 pg/ml in 31.1 % of acute ischemic stroke patients. Mean plasma BNP level was (74.76±52.96 pg/ml) in acute ischemic stroke patient. Significant negative correlation was found between concentration of plasma BNP and time passed in days from first appearance of stroke symptoms (r = - 0.791; p < 0.001). Conclusion: Plasma BNP level was significantly associated with baseline severity of acute ischemic stroke. Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 85-91